CHALLENGES AND FUNDING STRATEGIES FOR DIGITAL EDUCATION IN EUROPEAN PRIMARY SCHOOLS - Adrian ANDRONIC (Eastern European Journal of Regional Studies)
This paper focuses on digital education in European primary schools, examining trends, challenges, and financing strategies. The study uses a combination of research methods, including the comparative method, analysis, synthesis, induction and deduction, statistical data collection, and the monographic method. The paper identifies the current state of digital education in primary schools across Europe and highlights the challenges faced by educators and policymakers in implementing digital education initiatives. It analyzes the different financing strategies adopted by European countries and their effectiveness in promoting digital education in primary schools. The study finds that while many European countries have made significant progress in digital education, there are still challenges to be addressed, including infrastructure and connectivity issues, digital skills gaps, and funding constraints. The paper concludes with recommendations for policymakers and educators to promote digital education in primary schools and ensure that all students have access to quality digital learning opportunities.